Tinjauan Onkogenesis dan Morfologi Glioblastoma Multiforme - Elvina M. C. Pangestu; Meilany F. Durry; Maria Sambuaga (eBiomedik, 2022)
Abstract: Glioblastoma Multiforme (GBM) is a brain tumor which in its oncogenic process involves many oncogenes. Recent studies have discussed new oncogenes that play roles in GBM oncogenesis. GBM also have a variety of microscopic appearances. The aim of this study is to review recent studies regarding GBM oncogenesis and morphology. The design of this study is literature review and PICOS framework as the selection criteria. Glioblastoma stem-cells (GSC) play an important role in the oncogenesis of GBM. GSC cell-surface markers, signaling pathways, components resulting from the hypoxic microenvironment, components that induce GBM vascularization and the presence of proteins that play a role in GBM oncogenesis. Abnormalities in GBM are located in 4 regulatory genes that cause rapid growth of GSC without the ability to stop, hence a tumor lesion appears. The morphology featured in this study are small cell GBM, giant cell GBM and epithelioid GBM. The diagnostic markers of GBM are nuclear necrosis, cell palisade, microvascular proliferation, atypical nuclei, and high mitotic.Keywords: Oncogenesis; Morphology; Glioblastoma MultiformeÂ Abstrak: Glioblastoma Multiforme (GBM) merupakan sebuah tumor pada jaringan otak yang dalam proses onkogenesisnya melibatkan banyak onkogen. Banyak studi terkini yang membahas mengenai onkogen baru yang berperan dalam onkogenesis GBM. Tumor ini juga memiliki gambaran mikroskopik yang beragam. Penelitian ini bertujuan untuk meninjau studi terkini mengenai onkogenesis dan morfologi GBM. Desain penelitian yang digunakan dalam penelitian ini adalah literature review dengan menggunakan kriteria seleksi PICOS framework. Glioblastoma stem-cells (GSC) memainkan peran yang penting dalam onkogenesis GBM. Cell-surface markers GSC, signaling pathways, komponen yang dihasilkan dari hypoxic microenvironment, komponen yang menginduksi vaskularisasi GBM serta protein-protein tertentu, merupakan faktor-faktor yang berperan dalam onkogenesis GBM. Abnormalitas pada GBM terletak pada 4 regulator gen dan menyebabkan terjadinya pertumbuhan GSC tanpa kemampuan untuk menghentikan pertumbuhan sehingga munculah sebuah lesi tumor. Pada morfologi mikroskopik ditemukan gambaran GBM small cell, GBM giant cell dan GBM epiteloid. Penanda diagnosis GBM adalah inti nekrosis, palisade sel, proliferasi mikrovaskular, inti atipik, serta jumlah aktivitas mitosis yang tinggi.Kata kunci: Onkogenesis; Morfologi; Glioblastoma Multiforme